Quality of antenatal care services in Afghanistan: findings from the national survey 2022–2023 - Essa Tawfiq; Muhammad Haroon Stanikzai; Zabihullah Anwary; Khalid Akbari; Hadia Sayam; Abdul Wahed Wasiq; Omid Dadras (BMC Pregnancy and Childbirth)
Abstract Background The optimum use of antenatal care (ANC) services can reduce pregnancy-related complications and deaths. However, there is limited information on the quality of ANC services in Afghanistan. This study aimed to assess the quality of ANC services and examine the influence of sociodemographic factors on the quality of ANC services received by pregnant women in Afghanistan. Methods This study analyzed the data from the 2022–23 Afghanistan Multiple Indicators Cluster Survey (MICS), including 9,243 ever-married women aged 15–49 years who had given birth two years prior to the survey. ANC quality was classified as "good" if a woman had at least four ANC visits, initiated ANC during the first trimester, and received all four essential ANC services. Binary logistic regression was employed to examine the likelihood of receiving good-quality ANC across various sociodemographic variables. Results Only 6.2% of women received good-quality ANC. Factors significantly associated with receiving good-quality ANC included woman’s secondary (AOR:1.87, 95%CI: 1.33–2.63) and higher education levels (AOR: 1.75, 95%CI: 1.01–3.03), household head’s higher education level (AOR:1.63, 95%CI: 1.11–2.40), and wealth status (1.71, 2.26, 1.92, and 1.97 higher odds of receiving good-quality ANC for 2nd, 3rd, 4th, and 5th as compared to 1st quintiles of wealth, respectively). Conclusion The low utilization of good-quality ANC among women in Afghanistan, particularly among those at lower wealth status, with low education levels, underscores the need for targeted interventions to improve access and utilization of antenatal care services.